High-quality nodule analysis in spheroidal graphite cast iron using X-ray micro-computed tomography (Fracture and Structural Integrity, 2022)
This work is a continuation of the studies presented in a recent paper by the authors, where a methodology to obtain different nodule quality categories in spheroidal graphite cast iron, was proposed. In this study, an exhaustive analysis of the highest-quality graphite nodules was performed. The experimental methodology involves X-ray micro-computed tomography analysis and digital image post-processing of the high-quality graphite nodule population. Furthermore, different subpopulations were selected, following a nodular size criterion. The procedure involves the evaluation and comparison of the sphericity and compactness distributions and the distances between neighbouring nodules by using ad-hoc image processing software. The results reveal the complementary nature of the sphericity and compactness parameters, which allow classifying, with great accuracy, different nodular quality categories of spheroidal graphite cast iron. Additionally, new viewpoints about the nodular morphology study and the distribution of quality nodules in the metallic matrix was provided, which could be extended to other heterogeneous materials.
Keywords: X-ray micro-tomography; Sphericity; Compactness; Nondestructive analysis; Spheroidal graphite cast iron